Quantifying the effects of mixing and residual circulation on trends of stratospheric mean age of air. Issue 6 (27th March 2015) - Ploeger, F.; Abalos, M.; Birner, T.; Konopka, P.; Legras, B.; Müller, R.; Riese, M.
Abstract It is an outstanding issue to what degree trends in stratospheric mean age of air reflect changes in the (slow) residual circulation and how they are affected by (fast) eddy mixing. We present a method to quantify the effects of mixing and residual circulation on mean age trends, based on simulations with the Chemical Lagrangian Model of the Stratosphere (CLaMS) driven by ERA‐Interim reanalysis and on the integrated tracer continuity equation. During 1990–2013, mean age decreases throughout most of the stratosphere, qualitatively consistent with results based on climate model simulations. During 2002–2012, age changes show a clear hemispheric asymmetry in agreement with satellite observations. We find that changes in the residual circulation transit time cannot explain the mean age trends, and including the integrated effect of mixing is crucial. Above about 550 K (about 22 km), trends in the mixing effect on mean age appear to be coupled to residual circulation changes.